Study about the Expression of CypA Proteins and Its Blocking Effect in the Cerebellum from FMR1 Gene Knockout Mice by Electroacupuncture of DU1 Acupoint - Dong LIN; Wanping BU; Xiaoting YANG (康复学报)
Objective:To observe the effect of DU1 acupoint on the expression of CypA-ERK1/2 pathway related proteins from the cerebellum of FMR1 gene knockout (KO) mice, so as to explore its mechanism.Methods:Identification of murine gene phenotype by polymerase chain reaction (PCR), and choosing a Fragile X-1(FMR1) deficiency in the KO mice with 28 days after birth, total 24 KO mice were randomly divided into blank group, DU1 acupoint group, DU1 acupoint group with blocking and non-acupoint group, with 6 mice in each group. The blank group was given grab action, the other groups were taken acupuncture intervention. The expression of the related proteins of cerebellar CypA, P-ERK1/2 and ERK1/2 was detected by Western blot method.Results:The expression of CypA in the DU1 acupoint group was significantly higher than that of the non-acupoint group and the blank group (P<0.05). The expression of P-ERK1/2 in the DU1 acupoint group and the non-acupoint group was significantly higher than that of the blank group (P<0.05); the expression of ERK1/2 in the DU1 acupoint group was higher than that of the non-acupoint group and the blank group (P<0.05). The relative protein expression of the DU1 acupoint group with blocking can be converted by PD98059.Conclusion:Acupuncture on DU1 acupoint can promote the expression of CypA-ERK1/2 pathway related proteins in the cerebellar region of FMR1 gene KO mice, and this effection can be broken off by the blocker PD98059.